Communication to Find Water Intake Location within Public Private Partnership between Tangerang Government Authority and PT Aetra Air Tangerang - Binsar Naipospos; Aulia Paramita (The Institute for Research and Community Services, Institut Teknologi Bandung, 2019)
This article aimed to explore an effective communicative planning approach in infrastructure development using the PPP scheme, incorporating the complementary concepts of communicative planning and critical pragmatism. From 2005 to 2007, an epidemic disease severely threatened the District of Tangerang, which was found to be caused by poor water quality and improper clean water management. The limited local government budget and capability was a double issue that encouraged the participation of the private sector in building a drinking water infrastructure by using a public private partnership (PPP) scheme. One of the scopes of the project was finding the best tapping intake location for the Drinking Water Supply System (SPAM